2017
DOI: 10.1016/j.eurger.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The association between clinical frailty and walking speed in older hospitalized medical patients: A retrospective observational study

Abstract: This study aims to further evaluate the use of the clinical frailty scale (CFS) by assessing its correlation with usual walking speed (UWS) in older medical inpatients. Methods Retrospective observational study in an English tertiary university hospital. We analysed all admission episodes of people admitted to the Department of Medicine for the Elderly wards during a 3-month period. We excluded those who died or had a CFS score of 9, indicating terminal illness. The CFS was recorded on admission and 6 meter UW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Badrawasi and colleagues 79 found that rapid pace gait speed was a significant frailty predictor. Hartley and colleagues 87 reported a strong association between higher admission Clinical Frailty Scale (CFS) 120 and lower discharge usual gait speed (OR: 0.57; 95% CI: 0.50–0.65), not explained by variation in age, sex, presence of cognitive impairment, or illness acuity, thus providing the CFS maybe a valid measure of frailty in clinical settings. Lee and colleagues 90 found that while use of either gait speed or grip strength alone was sensitive and specific as a proxy for the Fried frailty phenotype, the dual‐trait measure of gait speed with grip strength was accurate, precise, specific, and more sensitive than individual traits and other possible dual‐factor combinations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Badrawasi and colleagues 79 found that rapid pace gait speed was a significant frailty predictor. Hartley and colleagues 87 reported a strong association between higher admission Clinical Frailty Scale (CFS) 120 and lower discharge usual gait speed (OR: 0.57; 95% CI: 0.50–0.65), not explained by variation in age, sex, presence of cognitive impairment, or illness acuity, thus providing the CFS maybe a valid measure of frailty in clinical settings. Lee and colleagues 90 found that while use of either gait speed or grip strength alone was sensitive and specific as a proxy for the Fried frailty phenotype, the dual‐trait measure of gait speed with grip strength was accurate, precise, specific, and more sensitive than individual traits and other possible dual‐factor combinations.…”
Section: Resultsmentioning
confidence: 99%
“…Garcia‐Cifuentes and colleagues 85 reported that Colombian older adults who had low handgrip strength and gait speed had an increased risk to suffer of cognitive impairment, regardless of age, sex, education, or body mass index (OR: 2.76; 95% CI: 1.83–4.15). Hartley and colleagues 87 reported a relationship between the pre‐admission levels of frailty, as assessed by the CFS, which is based on clinical judgement, and objectively measured usual walking speed, assessed on the day of discharge from hospital. They observed a strong association between higher admission CFS and lower discharge usual walking speed, regardless of variation in age, sex, presence of cognitive impairment, or illness acuity.…”
Section: Resultsmentioning
confidence: 99%
“…ENMO values were used from the lower leg accelerometer to define whether or not a person was moving (when already determined to be standing according to the positional criteria). Our previous work has determined usual walking speeds in this population at the point of hospital discharge as 0.33 m/s (IQR 0.21–0.50 m/s), a very low speed compared to those reported in community based samples [ 34 ]. A cut-off of ENMO value of >13 milligravity units (mg) from the accelerometer on the lower leg was used to define a participant as “moving”.…”
Section: Methodsmentioning
confidence: 99%
“…In older patients, life expectancy and quality of life after an acute event depend not only on the event itself, but also on several factors related to their general conditions such as frailty [28], capability [29], drug burden [30] and comorbidities [5]. The latter have a well-known role in the outcome of patients with an acute neurological event [24,25,26].…”
Section: Discussionmentioning
confidence: 99%